Antioxidant and Anti-Inflammatory Activities of High-Glucosinolate-Synthesis Lines of Brassica rapa - Hyunjin Choi; Hail Kim; Sanghee Han; Hyun Woo Park; In Jin Ha; Jung Sun Kim; Seok-Geun Lee (MDPI AG, 2023)
Excessive oxidative stress and inflammatory responses are associated with the development of various diseases, including cancer. Glucosinolates (GSLs) are phytochemicals known for their antioxidant properties, and doubled haploid lines (DHLs) of Brassica rapa with high GSL contents (HGSL) were intentionally developed from two edible subspecies of Brassica rapa: B. rapa subsp. trilocularis and B. rapa subsp. chinensis. The purpose of the present study is to assess the capacity of HGSL DHLs to mitigate oxidative stress and inflammation in lipopolysaccharide (LPS)-stimulated RAW264.7 cells, compared to pak choi as a parental control. Our findings demonstrate that HGSL DH lines effectively suppressed the expression of inducible nitric oxide synthase, leading to the reduced levels of nitric oxide at non-toxic concentrations. Additionally, these lines exhibited scavenging activity against reactive oxygen species and free radicals. The enhanced antioxidant capacity of HGSL DHLs was mechanistically attributed to the upregulation of antioxidant enzymes, such as NADPH quinone oxidoreductase 1 (NQO1), the glutamate-cysteine ligase catalytic subunit (GCLC), and heme oxygenase-1 (HMOX1). Furthermore, we confirmed that these effects were mediated through the nuclear factor erythroid 2-related factor 2 (NRF2) signaling pathway via p38 phosphorylation. Moreover, HGSL DHLs demonstrated inhibitory effects on pro-inflammatory cytokines and signal transducers and activators of transcription 3 (STAT3) phosphorylation. Collectively, our results indicate that HGSL DHLs possess better antioxidant and anti-inflammatory properties compared to the parental control pak choi in LPS-stimulated RAW264.7 cells, suggesting that HGSL DHLs of Brassica rapa could be considered as a beneficial daily vegetable for reducing the risk of inflammation-associated diseases.